Medical Sociology - Hearn, Gesine (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course we will explore the role and meaning of medicine in modern societies. After discussing in depth the conceptual development of the field of medical sociology, we will focus our attention on the American health care system. We will also discuss issues of global health and future issues in health and medicine. A research component will conclude the course: you will be introduced to a recent health research project conducted at ISU, and you are invited to explore the dataset.